Impact of COVID-19 pandemic on prevalence of Clostridioides difficile infection in a UK tertiary centre. (February 2022) - Voona, Sanjana; Abdic, Heather; Montgomery, Ros; Clarkson, Annette; Twitchell, Hannah; Hills, Tim; Briggs, Steve; Crooks, Colin; Monaghan, Tanya M.
Abstract: Serious concerns have been raised about a possible increase in cases of Clostridioides difficile infection (CDI) during the COVID-19 pandemic. We conducted a retrospective observational single centre study which revealed that total combined community and hospital-based quarterly rates of CDI decreased during the pandemic compared to the pre-pandemic period. Highlights: Retrospective, single-centre study of impact of COVID-19 on C. difficile infection rates Case numbers identified from hospital databases and reported as quarterly rates Total CDI rates decreased compared with the pre-pandemic period 8 cases of co-infection highlight the need for continued antimicrobial stewardship